2011
DOI: 10.1007/s12013-011-9160-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIWI in Human Hepatocellular Carcinoma

Abstract: In this study, the investigation of the expression of HIWI and its protein in hepatocellular carcinoma (HCC) was performed, and the relationships between HIWI expression and the location of HCC metastases were analyzed. Sets of fresh HCC and matched adjacent normal hepatic tissue and paraffin-embedded tissue slides were provided by the hospital hepatology and pathology departments. RT-PCR, Western blot, and immunohistochemistry were performed to detect HIWI mRNA and protein. Correlations between HIWI expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…When combined, these results indicate presence of the piRNA pathway in human liver and its modulation during neoplastic transformation. This result is in line with those suggesting the potential of PIWI proteins as cancer diagnostic and prognostic markers [7], including a positive correlation between HIWI expression and liver tumor size and metastasis, matched by a negative one with survival rate [3941]. Furthermore, MAEL, a key gene in the piRNA biogenesis pathways, has been recognized as oncogene for its role in HCC development and progression [42].…”
Section: Discussionsupporting
confidence: 83%
“…When combined, these results indicate presence of the piRNA pathway in human liver and its modulation during neoplastic transformation. This result is in line with those suggesting the potential of PIWI proteins as cancer diagnostic and prognostic markers [7], including a positive correlation between HIWI expression and liver tumor size and metastasis, matched by a negative one with survival rate [3941]. Furthermore, MAEL, a key gene in the piRNA biogenesis pathways, has been recognized as oncogene for its role in HCC development and progression [42].…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have demonstrated that HiWi plays a key role in the development of tumors in cervical (19), colon (20), and liver cancer (21). Sun et al (15) also found that HIWI was expressed specifically in glioma tissues and cell lines, but its role and molecular mechanisms related to the development of glioma remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Note HIWI expression in hepatocellular carcinoma tissues was significantly higher than in adjacent normal hepatic tissue and was correlated with metastasis (Jiang et al, 2011). HIWI expression positively correlated with tumor size and metastasis and negatively correlated with survival rates in hepatocellular carcinoma cells and tissues .…”
Section: Liver Cancermentioning
confidence: 85%